The potential of HBV cure: an overview of CRISPR-mediated HBV gene disruption - Yao, Zhi Q.; Schank, Madison B.; Zhao, Juan; El Gazzar, Mohamed; Wang, Ling; Zhang, Yi; Hill, Addison C.; Banik, Puja; Pyburn, Jaeden S.; Moorman, Jonathan P. (Frontiers in Genome Editing, 2024)
This article reviewed the CRISPR/Cas9 technology to disrupt and inactivate HBV genome.We summarized the tools employed in designing guide RNAs (gRNAs) targeting HBV genomes, the vehicles used for expressing and delivering CRISPR/Cas9 components, the models used for evaluating CRISPR-mediated HBV gene disruption, the methods used for assessing antiviral and off-target effects induced by CRISPR/Cas9, and the prospects of future directions and challenges in leveraging this HBV gene-editing approach to advance the HBV treatment toward a clinical cure.